Successful closure of a large abdominal wall defect using endoscopic component separation technique in an infant with a giant ventral hernia after staged surgery for omphalocele - Miki Toma; Toshihiro Yanai; Shiho Yoshida (Surgical Case Reports)
Abstract Background The management of large abdominal wall defects, such as omphalocele or gastroschisis, remains a challenge for pediatric surgeons. Though several techniques have been described to repair those conditions, there is no procedure considered to be the standard worldwide. We report an infant girl with a giant ventral hernia after staged surgery for omphalocele in whom delayed closure of a large abdominal wall defect was performed successfully using “endoscopic component separation technique (ECST)” without serious complications. Case presentation A baby girl was admitted to our hospital because of a giant omphalocele, which had been prenatally diagnosed. The omphalocele was supraumbilical and included the entire liver. After staged surgery, a large abdominal wall defect was closed by skin, creating a giant ventral hernia. We performed endoscopic separation component technique (ECST) for the closure of her abdominal wall defect when she was 11 months of age. ECST was initiated with placement of a 5.0-mm port just above the inguinal ligament and under the external oblique muscle. The space between the external and internal oblique muscles was created by the insufflation pressure, and a second 5.0-mm port was placed at 1.0 cm below the inferior edge of the rib into the space. As the further dissection was carried, the aponeurosis of the external oblique muscle was identified as a white line, running vertically from the epigastrium to inguinal ligament. It was transected longitudinally using electrocautery over its full length. The same procedure was performed on the contralateral side and the abdominal wall was successfully closed. Postoperative course was uneventful. Conclusions The technique of ECST, described here, is simple and safe for infants, and the cosmetic result is satisfactory.